TRPM7 Induces Tumorigenesis and Stemness Through Notch Activation in Glioma - Wan, Jingwei; Guo, Alyssa Aihui; King, Pendelton; Guo, Shanchun; Saafir, Talib; Jiang, Yugang; Liu, Mingli (Frontiers in Pharmacology, 2020)
OWe have reported that transient receptor potential melastatin-related 7 (TRPM7) regulates glioma stem cells (GSC) growth and proliferation through Notch, STAT3-ALDH1, and CD133 signaling pathways. In this study, we determined the major contributor(s) to TRPM7 mediated glioma stemness by further deciphering each individual Notch signaling. We first determined whether TRPM7 is an oncotarget in glioblastoma multiforme (GBM) using the Oncomine database. Next, we determined whether TRPM7 silencing by siRNA TRPM7 (siTRPM7) induces cell growth arrest or apoptosis to reduce glioma cell proliferation using cell cycle analysis and annexin V staining assay. We then examined the correlations between the expression of TRPM7 and Notch signaling activity as well as the expression of GSC markers CD133 and ALDH1 in GBM by downregulating TRPM7 through siTRPM7 or upregulating TRPM7 through overexpression of human TRPM7 (M7-wt). To distinguish the different function of channel and kinase domain of TRPM7, we further determined how the α-kinase-dead mutants of TRPM7 (α-kinase domain deleted/M7-DK and K1648R point mutation/M7-KR) affect Notch activities and CD133 and ALDH1 expression. Lastly, we determined the changes in TRPM7-mediated regulation of glioma cell growth/proliferation, cell cycle, and apoptosis by targeting Notch1. The Oncomine data revealed a significant increase in TRPM7 mRNA expression in anaplastic astrocytoma, diffuse astrocytoma, and GBM patients compared to that in normal brain tissues. TRPM7 silencing reduced glioma cell growth by inhibiting cell entry into S and G2/M phases and promoting cell apoptosis. TRPM7 expression in GBM cells was found to be positively correlated with Notch1 signaling activity and CD133 and ALDH1 expression; briefly, downregulation of TRPM7 by siTRPM7 decreased Notch1 signaling whereas upregulation of TRPM7 increased Notch1 signaling. Interestingly, kinase-inactive mutants (M7-DK and M7-KR) resulted in reduced activation of Notch1 signaling and decreased expression of CD133 and ALDH1 compared to that of wtTRPM7. Finally, targeting Notch1 effectively suppressed TRPM7-induced growth and proliferation of glioma cells through cell G1/S arrest and apoptotic induction. TRPM7 is responsible for sustained Notch1 signaling activation, enhanced expression of GSC markers CD133 and ALDH1, and regulation of glioma stemness, which contributes to malignant glioma cell growth and invasion.